Alternative solar-battery charge controller to improve system efficiency - Sabry, Ahmad H.; Wan Hasan, Wan Zuha; Ab Kadir, Mohd Zainal Abidin; Mohd Radzi, Mohd Amran; Shafie, Suhaidi (Trans Tech Publications, 2015)
This paper proposed a high efficiency solar-battery charge controller as an alternative to that controller which is used in most conventional residential solar system , the concept of the proposed controller circuit based on using the off state energy duration of the overcharge current in a separate path, this energy delivers to auxiliary battery or direct load, such as fans, used to cool or ventilate the system components and consequently improving system performance, where the overcharge current refer to that current available stand by when the battery fully charged or reached its maximum charge voltage. It is avoided here that power losses coming from the main switching component and complexity of the conventional controller, this will leads to new electronic circuit with low losses as a compared with the conventional charge controller to be a part of the integrated and automated building solar system, the design has an algorithm based on some environment parameters like sun Irradiance and weather temperature, this algorithm seems to be inversely calculated because its start from the value of full charge battery voltage, the practical results shows the improvements if compared with other methods. A Simulink Matlab simulator is attempted in the simulation phase of this research as well as an experimental data has been collected to verify the circuit function and energy saving goal.